MANAGEMENT OF ACTIVE CYCLE OF BREATHING TECHNIQUES (ACBT) AND POSTURAL DRAINAGE IN BRONCHIECTASIS: A CASE STUDY - Halim, Muhammad; Sudaryanto, Wahyu Tri (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Bronchiectasis is a debilitating chronic respiratory condition that affects people of all ages. It is most common in women and those older than 60 years, Patients have daily excessive sputum and associated symptoms, recurrent chest infections and impaired healthrelated quality of life Case Presentation: The patient is a 54 year old woman with a history of bronchiectasis, complaining of shortness of breath, cough accompanied by phlegm that has been felt since 6 months ago. Management and Outcome: Interventions were given in the form of Active Cycle of Breathing Techniques (ACBT) and Postural Drainage and the therapy process was carried out in 3 meetings. Examination of the degree of cough with the Leicester Cough Questionnaire, examination of the thoracic cage with anthropometry with 3 measurement reference points, namely the axilla, Intercostal IV-V, and xiphoid process, and measurement of functional activity level with the Modified Medical Research Council (MMRC). There was an increase in the difference in expansion of the thoracic cage at each axillary point, Intercostal IV-V, and xiphoid process from T1: 1 cm to T3: 2 cm. on the measurement of the degree of cough with the Leicester Cough Questionnaire there was an increase in the value from T1:7 to T3:12, and the measurement of functional activity level with the Modified Medical Research Council (MMRC) decreased from T1:3 to T2:2. Discussion: ACBT that performed in 3 stages, can reduce airway constriction and increase oxygen saturation through breathing control, thoracic expansion exercises that move secretions and increase alveolar ventilation, and the huffing or force expiratory technique (FET) which helps move phlegm from the small airways into the airways. big air. This is also assisted by postural drainage, which is positioning the patient with the lung segment where there is a buildup of sputum in such a way that gravity has a maximum effect on facilitating the drainage of broncho-pulmonary secretions from the tracheobronchial tree. Conclusion:Active Cycle of Breathing Techniques (ACBT) and Postural Drainage can help treat complaints in cases of Bronchiectasis such as clearing the airway, increasing the expansion of the thoracic cage, and increasing the ability of functional activities.